2017
DOI: 10.3390/su9020164
|View full text |Cite
|
Sign up to set email alerts
|

A Report on the In Vitro Antioxidant Properties of Vachellia karroo Leaf Extract: A Plant Widely Grazed by Goats in the Central Eastern Cape of South Africa

Abstract: Abstract:The polyphenolic constituents and antioxidant activity of aqueous and acetone extracts of Vachellia karroo leaves were determined in order to evaluate its efficacy in scavenging radicals such as DPPH, ferric reducing power and nitric oxide as an antioxidant model. The flavonols and flavonoid and phenolic content of the leaf extracts were also accessed using benchmark phytochemical reaction methods. Results of the phytochemical analyses revealed the presence of flavonoids and flavonol and phenolic comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 20 publications
2
8
0
Order By: Relevance
“…This means that at these low concentrations, the extracts may all be used in replacement of ascorbic acid in cases where there is the scarcity of it. The NO • inhibitory activity of acetone, ethanol, boiled and cold aqueous extracts being higher than that of BHT (Table 2) indicates the comparative ability of the extracts to reduce oxidative damage to certain vital tissues in the body, this is in agreement with several other works done on other species of Helichrysum in which similar phytochemicals and antioxidants are present [45,46].…”
Section: Discussionsupporting
confidence: 88%
“…This means that at these low concentrations, the extracts may all be used in replacement of ascorbic acid in cases where there is the scarcity of it. The NO • inhibitory activity of acetone, ethanol, boiled and cold aqueous extracts being higher than that of BHT (Table 2) indicates the comparative ability of the extracts to reduce oxidative damage to certain vital tissues in the body, this is in agreement with several other works done on other species of Helichrysum in which similar phytochemicals and antioxidants are present [45,46].…”
Section: Discussionsupporting
confidence: 88%
“…The nitric oxide inhibitory activities of the acetone, ethanol, boiled and cold aqueous extracts being higher than that of the BHT Table 2 indicate the comparative ability of the extracts to reduce oxidative damage to some vital tissues in the body; this is in agreement with several other works that have been done on other Helichrysum species in which similar phytochemicals and antioxidant activities as found in this study were reported 45,46 . Since NO also plays an important role in the pathogenesis of inflammation 47 , H. petiolare, may, therefore, be quite effective in the treatment of hyperglycemia-induced inflammation and wound healing.…”
Section: Fig 1: Total Antioxidant Capacities Of Ascorbic Acid Bht Cold and Boiled Aqueous Acetone And Ethanol Whole Plant Extracts Ofsupporting
confidence: 92%
“…Total antioxidant activity of the extract was evaluated according to pre-described assay [ 17 ] with slight modifications. A volume of 100 μL acetone extract was incorporated into 100 μL of 0.135 mM DPPH dissolved in 80 % (v/v) acetone.…”
Section: Methodsmentioning
confidence: 99%